2020
DOI: 10.1186/s12302-020-00336-3
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-like fluorescence as a fingerprint of dry-weather misconnections into storm drainage system

Abstract: Background: Inappropriate dry-weather misconnections into storm drainage system are a demanding environmental problem worldwide, which leads to unexpected dry-weather discharge into surface waters. It often costs a large amount of manpower and resources to identify the source of misconnections and estimate its contributions. In this study, we evaluated the possibility of quantifying proportional source contribution in a storm drainage system with dry-weather misconnections from domestic sewage and river water … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The emission wavelength at 270 nm in synchronous spectroscopy indicated the presence of tyrosine-like component ( Barker et al., 2009 ; Lu et al., 2021 ). This component could be predominantly originated from biodegraded or decomposed aquatic plants through biological activities ( Lu et al., 2021 ; Yin et al., 2020 ). The intensity of this substance was maximum in Kotka (5492 AU) and minimum in Harbaria (2035 AU) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The emission wavelength at 270 nm in synchronous spectroscopy indicated the presence of tyrosine-like component ( Barker et al., 2009 ; Lu et al., 2021 ). This component could be predominantly originated from biodegraded or decomposed aquatic plants through biological activities ( Lu et al., 2021 ; Yin et al., 2020 ). The intensity of this substance was maximum in Kotka (5492 AU) and minimum in Harbaria (2035 AU) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is approximately 0.2-0.3 billion tons of TPDW discharged into aquatic environment in SJ region per year ( Xie and Ruan, 2013 , Jiangsu Provincial Bureau of Statistics 2019 ). Hence, the ratiocination from ( Yin et al, 2020 ) seemed reasonable. However, they did not try to confirm their inference.…”
Section: Resultsmentioning
confidence: 89%
“…In other surface water bodies of SJ region, several previous studies also found fluorescence features that were similar to those of water body in SJ-BHGC ( Qiu et al, 2012 , Yao et al, 2016 , Zhou et al, 2018 ). ( Yin et al, 2020 ) stated that the main sources of FDOM in water bodies of SJ region were probably related to the discharge of TPDW. The TPDI is a traditional pillar industry in Jiangsu Province and SJ is the area with the highest TPDI density in China ( Liu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that there is high abundance of protein-like components in the Huangpu River, which flows into the Yangtze River between YE3 and YE4 (Dong et al, 2014). In addition, protein-like fluorescence components were found to be enriched in domestic wastewater (Yin et al, 2020), and one large wastewater treatment plant with a wastewater loading of 2.8 million m 3 /d is located nearby YE6. Therefore, the increase of C1 could be possibly attributed to the inputs of the Huangpu River (YE3 station) and the domestic wastewater treatment plant (YE6 station).…”
Section: Discussionmentioning
confidence: 99%